It will be journalism? Journalism students’ perceptions of the journalistic field in today’s and future world - Silvestre, Cláudia (2022)
This proposal is based on the analysis and interpretation of the results of a survey, in the 2019-2020 school year, to undergraduate and master’s students in Journalism at the academic institutions of Lisbon, about their perceptions of the journalistic field and its role in a democratic society. Journalism is meant to place the public good above all else and is still based on ethical values, such as truth, balance, accuracy, objectivity - journalists must report the news in the public interest, striving not to let their preconceptions interfere with their stories. However, “the big picture” has changed in many ways. Framed by this new media ecology, instead of having time to fact check, journalists are urged to be the first to break the story, because the audience must have the news in mere seconds. As we know, this pressure often leads to misinformation being published, causing significant damages into the public opinion and, consequently, in their behavior. Are the future journalists aware of this impact? How do they perceive their responsibility as agents of change? Also, in a scenario often drawn “in black” either by journalists and media researchers, mainly referring to reconfigurations of newsrooms, the precariousness of job contracts, the power economic interests, the shortening of time and space to gather and treat information, what do the future journalists think about these topics and how intend to deal with these constraints? Four decades after the birth of the first graduation on media studies in Portugal, at Universidade Nova de Lisboa, most of the Portuguese journalists have an academic degree (in Journalism or other scientific field), which means a remarkable change, not only in the way of entering the profession but also in the way of thinking and practicing “the” journalism. The survey is structured in tree parts, each one referring to the different dimensions of the analysis: diagnosis, intentions and expectations. In the first one, the questions focus on student’s self-perceptions about what journalism is nowadays and its role in society. In the second one, students answer about how they perceive their intervention in the public debate as future journalists and/or academic researchers. The third one challenges students to point out expectations about what journalism(s) will emerge from the disorder of the political and civic public space. The answers of around 200 respondents to these questions led us to identify the self-perceptions of journalism students as candidates to a challenging mission and to purpose new paths to academic research and education.